The BFG - Dahl, Roald (UK Puffin books, 1982)
The BFG' is based on Roald Dahl's novel. Sophie can't sleep: looking out the window, she sees a giant blowing dreams into children's heads through their bedroom windows. Having been spotted, the Big Friendly Giant grabs Sophie and takes her back to his cave, where they eat snozzcumbers and drink frobscottle, before galloping off to Dream Country to collect some dreams. To save the people of England from being eaten up by the man-eating giants, Sophie and the BFG must concoct a dream that will persuade the Queen to believe in evil giants, so that with the help of the army and the air force, they might be rid of them once and for all